1979
DOI: 10.1073/pnas.76.12.6439
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial plasmalemmal vesicles as elements in a system of branching invaginations from the cell surface.

Abstract: In electron microscopy studies of the endothelial vesicles in frog mesenteric capillaries, an accidental observation was made concerning vesicular organization. When tannic acid was added to already fixed tissue, the mordant reached apparently free vesicles in the cytoplasm under conditions in which vesicular movement was excluded and in which the impermeability of the cell membranes was preserved. This indicates a spatial continuity between the vesicles and the cell exterior. It is proposed that cytoplasmic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(64 citation statements)
references
References 29 publications
0
63
1
Order By: Relevance
“…Alternatively, a pathway of endosomal internalization and subsequent retroendocytosis of the HDL particle after enrichment with cholesterol has been suggested in rat hepatoma cells and macrophages by several investigators (5, 30); however, direct visualization of the distribution of HDL in cholesterol-loaded cells has been lacking. The vesicular structure of the endothelial cells and their role in vesicular transport have been questioned for many years (31). People argue that at least some of the vesicles revealed under the electron microscope appeared to be surface membrane invaginations instead of free vesicles; however, due to the limitation of microscopic techniques, there was no consensus until the invention of confocal microscopy in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a pathway of endosomal internalization and subsequent retroendocytosis of the HDL particle after enrichment with cholesterol has been suggested in rat hepatoma cells and macrophages by several investigators (5, 30); however, direct visualization of the distribution of HDL in cholesterol-loaded cells has been lacking. The vesicular structure of the endothelial cells and their role in vesicular transport have been questioned for many years (31). People argue that at least some of the vesicles revealed under the electron microscope appeared to be surface membrane invaginations instead of free vesicles; however, due to the limitation of microscopic techniques, there was no consensus until the invention of confocal microscopy in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Chains of two or three vesicles were rare (arrows) and complexes that could be dendritic structures of the type previously described (10)(11)(12) were only occasionally encountered (double alTOWS).…”
Section: Resultsmentioning
confidence: 99%
“…In support of the existence of tubular systems are results obtained from cryofixation-cryosubstitution experiments in which cellular structures are rapidly immobilized (Frokjaer-Jensen et al 1988). In such tissues, as well as in those fixed in the presence of tannic acid (Bundgaard et al 1979), virtually all the apparent free plasmalemmal vesicular profiles present in endothelial cell cytoplasm were reported to be interconnected, forming an integral part of channel-like structures (Bundgaard et al 1979;Frokjaer-Jensen et al 1988). In addition, in permeability studies it was found that tracer proteins of different molecular weights display differences in permeability coefficients, indicating that transport is compatible with diffusion processes rather than with vesicular bulk quanta movement from one cell front to the other (Bundgaard 1980;Bendayan and Rasio 1996a,b).…”
Section: Figurementioning
confidence: 99%